DEMOGRAPHIC PROFILE OF DISABILITY ASSESSED PATIENTS IN TERTIARY CARE HOSPITAL IN PRATAPGARH DISTRICT OF UTTAR PRADESH - KUMAR, SACHIN; SINGH, VINEET; SINGH, JITENDRA PRATAP; MAHESH KUMAR NAVADAYA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: There is a lack of data regarding the demographic profile of acquired disability in hospital-admitted patients in Pratapgarh District. Therefore, the present study was conducted to know the demographic profile of disability-assessed patients in a tertiary care hospital of Pratapgarh district. Methods: The present study is a record-based retrospective study in which 490 patients assessed by the investigator for disability in selected tertiary care hospitals in Pratapgarh district of Uttar Pradesh between 2020 and 2023 were taken into consideration. Demographic parameters like age, gender, number of admissions, duration of hospital stay, etc. were recorded in a Microsoft Excel sheet. Data were analyzed by descriptive statistics using SPSS version 23.0 and presented as graphs. Results: Out of 490 cases, the majority (83.06%) were male, while 16.94% were female. The mean age of patients was 38.2±3.7 years. In the present study, males had a mean disability percentage of 28% (standard deviation, SD=24.9) and females had a mean disability percentage of 22% (SD=18.3). In the majority of patients (75.3%), one-time admission was observed. In the present study, the majority of cases (94.89%) had a history of road traffic accidents. About three-fourths of disabilities (75.51%) were found in brachial plexus injuries, followed by 46.94% of disabilities in spine injuries and 38.98% in head injuries. Conclusion: The present study will help treating doctors, especially orthopedic surgeons, insurance companies, and governments understand the magnitude of the problem. The treating doctor, especially orthopedic surgeons, will be in a better position to explain to patients about disability through its assessment, and the benefits will be available to patients in the form of certification.